CHEMOTACTOMETER AND GLUE TRAP BIOASSAYS TO EVALUATE PELLET BAITS TO LURE HOUSE FLIES - S.T. Bino Sundar; T.J. Harikrishnan; Bhaskaran Ravi Latha; T.M.A. Senthil Kumar; G. Sarath Chandra; A. Serma Saravana Pandian; C. Pandian; K. Ambasankar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Different pellet baits were prepared and evaluated for their efficacy to lure house flies in chemotactometer and glue trap bioassays. Pellets with fish meal alone (FM), fish meal + (Z)-9-tricosene (FMP) and fish meal + (Z)-9-tricosene + butylated hydroxyl toluene (FMPB) were prepared. In the chemotactometer bioassay, house flies comprising of a mixed population of males and females were released into the four arm acrylic chemotactometer, acclimatized for 10 min and observed for 30 min. Out of the 201 house flies tested in six replicates, 65.17% (131 flies) responded to the baits. The attraction was maximum towards FMP  pellets (49.61%) followed by FMPB (25.19%) and FM pellets (8.39%) with least preference towards the unbaited control (11 flies, 8.39%). The per cent fly activity was 64.82%. Flies attracted towards FMP and FMPB pellets preferred to stay and spend more time inside the baited arms of the chemotactometer exhibiting wing fanning and mating behaviour. In the glue trap bioassay, a glue trap was fabricated in thermacol sheet of 20 cm L x 10 cm B x 3 cm H with a red glue sheet pasted on it and baited with pellet baits. The traps were then placed on the floor of the insectary containing house flies for 24 h. Out of 310 house flies trapped, maximum attraction was elicited towards FM pellets (29.35%, 91 flies) followed by FMPB (27.09%, 84 flies) and FMP pellets (25.48%, 79 flies) with least attraction towards unbaited control traps (18.06%, 56 flies). Results revealed that in the chemotactometer bioassay, more flies were attracted towards the pellet baits with (Z)-9-tricosene (FMP) followed by FMPB and FM pellets. In the glue trap bioassay, attraction was more towards FM pellets followed by FMPB and FMP pellets. Overall, male flies were found more attracted towards FMP and FMPB pellets. Both the bioassays were found efficient to evaluate the attractiveness of pellet baits for house flies and (Z)-9-tricosene incorporated in fish meal and molasses as pellet baits can be effectively used in house fly traps to improve trap efficiency.